Potential Roles of Serum Caveolin-3 Levels in Patients with Atrial Fibrillation - Sun, Ling-Yue; Qu, Xiang; Chen, Ling-Zhi; Zheng, Gao-Shu; Wu, Xin-Lei; Chen, Xing-Xing; Huang, Wei-Jian; Zhou, Hao (Frontiers in Aging Neuroscience, 2017)
Objective: To explore serum caveolin-3 (Cav-3) levels in patients with atrial fibrillation (AF) and to evaluate the role of Cav-3 as a biomarker for AF and incident heart failure (HF). Methods: 305 patients were enrolled in the study and divided into three groups: sinus rhythm (Group SR), paroxysmal AF (Group paAF) and persistent AF (Group peAF). Serum Cav-3 concentrations were measured by enzyme-linked immunosorbent assay at baseline. Clinical characteristics and laboratory data were collected during hospitalization, and a follow-up of 12-months was carried out. Results: Serum Cav-3 concentrations were significantly decreased on the Group SR and the highest concentrations of Cav-3 in patients were found on the Group peAF (516.7 ± 274.0 versus 609.3 ± 287.0 versus 688.3 ± 264.6 ng/L, P < 0.05). Left atrial diameter (LAD) in the Group peAF was significantly higher than in the Group paAF, and the Group SR had significantly lower LAD than the Group paAF and Group peAF. The risks of new-onset HF in the Group SR, Group paAF and Group peAF were 8.1%, 14.5% and 28.6%, respectively. There was a significant difference between the Group peAF and the other two groups. Serum Cav-3 concentrations were trisected in AF participants (lower tertile: ≤ 498, middle tertile: > 498-703, upper tertile: ≥ 703). In further tertile studies, subjects in the lower tertile of Cav-3 concentrations were more likely to become paroxysmal AF and had much lower LAD (P < 0.05). And in the middle and upper tertiles, participants with AF tended to suffer from HF compared to the lower group (P < 0.05). Conclusion: We provide evidence that Cav-3 has a significant meaning in AF patients. The levels of Cav-3 may be related to the LAD and new-onset HF. Key words: atrial fibrillation, caveolin-3, left atrial diameter, heart failure